DEVELOPMENT AND APPLICATION OF CASTING DISTORTION & COMPENSATION TECHNOLOGY BASED ON AUTOMATIC ITERATION METHOD - DR. XIAOJUN YANG; MS. RAJESHWARI SANJAY RAWAL (International Journal of Innovations in Engineering Research and Technology, 2021)
Casting warp or distortion is one of the main defects often encountered in the production of die-casting, it is also quite difficult to solve. The traditional methods have the problems of low efficiency, heavy workload and poor working environment. This paper introduced Cast-Designers newly developed distortion compensation solver DCS Distortion Compensation Solver, it can predict the casting distortion and warp in advance and find the casting products meet the tolerance requirements in the automatic iterative optimization technology. With such tools and technology, we can reduce the casting distortion effectively and meet the machining requirements directly.